Використання статистичних методів описової статистики у корпусній лінгвістиці - Кочуєва, Зоя; Дідусьов, Валерій (Видавництво Львівської політехніки, 2017)
The purpose of this study: the development of software to determine the criteria of Pearson Hi2 on the basis of both scientific and literary texts. In the first part of the study it is conducted the analysis of contemporary corpus linguistics. Statistical studies and their views of corpus linguistics are also described. Held his own description of the body of fiction and non-fiction texts. In the second part of the paper it is focused on statistical methods in corpus linguistics, namely the descriptive statistics. The description of the operation of the developed software.
Keywords: комп’ютерні науки; лінгвістичні аспекти; корпус; критерії; генеральна сукупність; вибірка